The Science And Practice Of Change: Engage Star Model For Measurable Organizational Change - Tourista, Meiko; Sutanto, Eddi; Azwir, Akbar (Faculty of Science and Technology University of Pramita Indonesia, 2025)
Organizational change remains the critical nexus between strategic intent and realized value, yet a significant proportion of transformations fail to achieve sustained benefits due to inadequate management of the human element. This paper introduces the ENGAGE Star Model, an integrated and measurable framework designed to systematically guide organizations through the complexities of behavioral and structural transition. Built upon a synthesis of established process standards and psychological adoption models, the ENGAGE Star Model operationalizes change management by focusing on six distinct stages of individual commitment and mastery: Enlighten, Nurture, Guide, Activate, Grow, and Embed. The model’s core contribution is its ability to translate abstract change principles into actionable, data-driven interventions. This research posits that by applying the iterative and human-centric ENGAGE framework, organizations can significantly improve adoption rates, mitigate resistance, and accelerate the realization of strategic benefits. The findings offer a practical and academically rigorous methodology for practitioners seeking to master the science and practice of measurable organizational change.